Preparation and Characterization of Self-Healing Polyurethane Powder Coating Using Diels–Alder Reaction - Negin Farshchi (MDPI AG, 2021)
Although powder coating systems offer many environmental, ecological and energy related benefits over liquid based coatings, in the case of uretdione based polyurethane systems, high curing temperature is still an issue. On the other hand, powder coating systems make it possible to reduce the costs and enhance the process of forming complex 3D structures using the deep drawing method by pre-coated metal substrates. During this processing method, there is a probability of micro crack formation in the coated film due to strain impact on the coating layer. A powder coating with self-healing ability is an ultimate solution to face not only this kind of fraction but also any other possible ones (such as defects caused by any impact on film surface during processing, transporting or even service). Here, a single molecule that is prepared via Diels–Alder cycloaddition reaction and retro Diels–Alder cleavage reaction was utilized as a self-healing additive to achieve self-healing ability in the powder coating system that is based on a commercially available uretdione cross-linker and OH-polyester resin. Coatings were prepared through melt mixing of components in a lab mixer, milling, sieving, and then application on the metal substrate through the electrostatic spraying method. To illustrate the role of self-healing additive, various concentrations (4 and 9% wt.) in combination with different curing temperatures (80 °C to 200 °C) were investigated. Both samples containing HA showed self-healing ability at elevated temperature around 120 °C for about 30 min with acceptable roughness and surface properties. Hardness measurement of cured film as well as thermal investigation indicate the chemical reaction of HA in a cross-linked network of cross-linker and resin. In addition, using HA leads to a 40 K drop in curing temperature of the system without using any catalyst. A 2.58% improvement in hardness values at a lower curing temperature and healing time of around 12.5 min at 120 °C to recover 100% of initial scratch (more than 10 cycles) in the sample containing 9% wt. HA was observed.